Spencer [videorecording (DVD)] - Knight, Steven, 1959-; Stewart, Kristen, 1990-; Spall, Timothy, 1957-; Farthing, Jack; Nielen, Jack; Spry, Freddie; Berrington, Elizabeth; Gonet, Stella; Manson, Amy, 1985-; Harkness, James (Actor); Harris, Sean, 1966-; Hawkins, Sally, 1976-; et al. (Decal Releasing, LLC, 2022)
During her Christmas holidays with the royal family at the Sandringham estate in Norfolk, England, Diana Spencer, struggling with mental health problems, decides to end her decade-long marriage to Prince Charles.